Steam reforming of formaldehyde on Cu (100) surface : a density functional study - Lin, Ming Yuan. (2010)
As concerns about rising fossil fuel prices, energy security, and climate change increase, alternative source of energy can play a key role in producing local, clean, and inexhaustible energy. A more viable alternative source of energy would be the employment of hydrogen. However, hydrogen cannot be stored easily. This led to the investigation of fuel cells that can produce hydrogen on board. Fuel cell, which is an electrochemical energy conversion device, has become a more environmentally friendly and realistic alternative to combustion engines. A hydrogen cell uses hydrogen as fuel and oxygen as oxidant, producing water as product, which does not harm environment. However, difficulties of transportation and danger of handling have been caused by hydrogen’s low density and large volume. Therefore, liquid fuel is preferred over gas fuel as they are more convenient and less dangerous to handle. Strong efforts have been made by researchers to achieve an efficient in situ conversion of liquid fuel to hydrogen. In this project, the main objective is to understand the reaction mechanism of formaldehyde steam reforming reactions on Cu (100) surface. A typical process for this purpose is methanol steam reforming (MSR) on Cu-based catalysts. On the catalyst, the formation of CO2 is thought to be via the route of formaldehyde reacting with water related species (i.e. OH and O) via a formate type intermediate on the Cu surface; instead of the iii decomposition of formaldehyde to CO followed by formation of CO2 via the water-gasshift reaction. A detailed understanding of the mechanism of formaldehyde steam reforming is necessary to provide indispensable guiding information for designing and producing new, more efficient steam reforming catalyst. Thus in this current works, we studied the kinetics and mechanism of formaldehyde steam reforming on the Cu (100) surface.